2019
DOI: 10.1007/s10654-019-00543-0
|View full text |Cite
|
Sign up to set email alerts
|

The major causes and risk factors of total and cause-specific mortality during 5.4-year follow-up: the Shanghai Changfeng Study

Abstract: To investigate the major causes and predictive factors of death in a middle-aged and elderly Chinese population. A total of 6591 residents aged ≥ 45 years from Shanghai Changfeng community were followed up for an average of 5.4 years. The causes of death were coded according to the 10th Revision of International Classification of Diseases. The mortality rate was calculated by person-years of follow up and age-standardized according to the 2010 Chinese census data. Multivariable-adjusted Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…Several potentially modifiable risk factors for non-CRC mortality were identified in this healthy CRC screening population, including increased number of medical comorbidities, smoking, and decreased physical activity. Previous studies in various populations have found consistent relationships between all-cause mortality and these risk factors, all with similar effect sizes to our study (11,18–29). Although these findings are not novel, several specific findings warrant additional consideration.…”
Section: Discussionsupporting
confidence: 91%
“…Several potentially modifiable risk factors for non-CRC mortality were identified in this healthy CRC screening population, including increased number of medical comorbidities, smoking, and decreased physical activity. Previous studies in various populations have found consistent relationships between all-cause mortality and these risk factors, all with similar effect sizes to our study (11,18–29). Although these findings are not novel, several specific findings warrant additional consideration.…”
Section: Discussionsupporting
confidence: 91%
“…For additional EJE references please see [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160].…”
Section: Main Results In the Last 3 Yearsunclassified
“…The inclusion criteria of participants were (1) aged over 45 years old and (2) lived in Shanghai Changfeng community for at least 5 years. As shown in the participant flow diagram (Figure S1), the vital status data of 6591 participants were available according to registration data from the Shanghai Center for Disease Control (CDC) at the end of 2016 21 . Among them, a total of 5689 participants were genotyped with an Illumina Infinium BeadChip genotyping array (707 180 markers), and after excluding 60 participants with unqualified genotype data and 48 with missing of serum biochemical or NMR‐based lipoprotein profile data, a total of 5581 participants were included for analysis, and 4645 participants with both liver ultrasonography and fibrosis 4 score (FIB‐4) data available were selected for subgroup analysis.…”
Section: Methodsmentioning
confidence: 99%